Genetic Variants of the MGAT5 Gene Are Functionally Implicated in the Modulation of T Cells Glycosylation and Plasma IgG Glycome Composition in Ulcerative Colitis - Pereira, MS (2020)
OBJECTIVES: The impact of genetic variants (single nucleotide polymorphisms [SNPs]) in the clinical heterogeneity of ulcerative colitis (UC) remains unclear. We showed that patients with UC exhibit a deficiency in MGAT5 glycogene transcription in intestinal T cells associated with a hyperimmune response. Herein, we evaluated whether MGAT5 SNPs might functionally impact on T cells glycosylation and plasma IgG glycome in patients with UC, as well as in UC clinical outcomes. METHODS: Three selected MGAT5 SNPs (rs3814022, rs4953911, and rs1257220), previously associated with severity of autoimmune disease or with plasma glycome composition in healthy individuals, were functionally evaluated in patients with UC through analysis of MGAT5 mRNA levels in colonic (n = 14) and circulating (n = 24) T cells and through profiling the plasma IgG Fc glycosylation (n = 152). MGAT5 SNPs were genotyped in 931 patients with UC from 2 European cohorts and further associated with patients' prognosis. Targeted next-generation sequencing for MGAT5 coding and regulatory regions was also performed. RESULTS: MGAT5 SNPs were shown to be functionally associated with low transcription levels of MGAT5 in colonic and circulating T cells from patients with UC and with agalactosylation of IgGs, often associated with a proinflammatory phenotype. The SNPs rs3814022 and rs4953911 were further associated with the need of biologics. Next-generation sequencing data further revealed a combination of MGAT5 SNPs that stratify patients with UC according to their severity. DISCUSSION: Our results revealed that MGAT5 SNPs have a phenotypic impact on T cells glycosylation and in plasma IgG glycome composition associated with UC pathogenesis. MGAT5 SNPs display a tendency in the association with a worse disease course in patients with UC.